Relacion entre la presencia de infecciones bacterianas en utero y oviductos de vacas de matadero - Palacios, R.=700 1 Rivas, M.; Jarpa, M.
(En, Es)
Ilus., 15 ref.
Keywords: GANADO BOVINO; ENFERMEDADES INFECCIOSAS; BACTERIOSIS; ESCHERICHIA COLI; MYCOBACTERIUM TUBERCULOSIS; MYCOPLASMA; UTERO; OVIDUCTOS; VACA; MATADEROS; CHILE; AGRICULTURA TECNICA